2008
DOI: 10.3238/arztebl.2008.0108
|View full text |Cite
|
Sign up to set email alerts
|

Visual Loss Following Intraocular Gas Injection

Abstract: Both doctors and patients need to be well informed about the hazards of intraocular gas application as good communication may prevent complications. If in doubt, the anesthesiologist should avoid nitrous oxide, in particular in the unconscious patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
0
17
0
1
Order By: Relevance
“…It has been shown that intravitreal SF 6 and especially C 3 F 8 can cause irreversible damage to the retina and impair retinal function in rabbits 5. Expanding gases have also been shown to cause breakdown of the blood–ocular barrier and may induce an inflammatory response due to mechanical damage,6–8 findings that were not evident with pure air 5 9. This may explain why previous studies,4 10–12 which showed good clinical success with expanding gas PR, have also shown a higher incidence of macular pucker and proliferative vitreoretinopathy (PVR) following PR with SF 6 and C 3 F 8 as compared to pure air 13…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that intravitreal SF 6 and especially C 3 F 8 can cause irreversible damage to the retina and impair retinal function in rabbits 5. Expanding gases have also been shown to cause breakdown of the blood–ocular barrier and may induce an inflammatory response due to mechanical damage,6–8 findings that were not evident with pure air 5 9. This may explain why previous studies,4 10–12 which showed good clinical success with expanding gas PR, have also shown a higher incidence of macular pucker and proliferative vitreoretinopathy (PVR) following PR with SF 6 and C 3 F 8 as compared to pure air 13…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, several materials, including air, sulphur hexafluoride (SF 6 ), perfluoropropane (C 3 F 8 ), perfluorocarbon liquids, silicone oil, and heavy silicone oil are commonly used as temporary vitreous substitutes. Although these substitutes have some important characteristics, such as optical clarity and chemical inertness, they are also associated with many drawbacks and limitations, such as elevating intraocular pressure (IOP) and fast intraocular absorption1, post-operative cataract, oil emulsification, secondary glaucoma and keratopathy23456, irreversible cell damage7, higher ametropia89, creating non-effective tamponade if the inferior retina breaks1011, and so on.…”
mentioning
confidence: 99%
“…Pressure increases can also occur in the middle ear or facial sinuses, the eye injected with air or sulfur hexafluoride, the ventricles of the brain when air is injected for example in pneumoencephalography. It can also cause damage to the eye from increase in pressure [50,51,52,53,54,55]. This also occurs in cases of air embolism, expanding its size [56,57].…”
Section: Diffusion Hypoxia and Filling Of Gas Containing Compartmentsmentioning
confidence: 99%